Impact of Employee Competence and Resilience on Job Performance: A Case Study of PT. Dharma Electrindo Manufacturing - Komalasari, Iin; Gunawan, Asep; Priyono, Dadang (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Purpose: This study aims to analyze the influence of employee competence and resilience on work performance at PT. Dharma Electrindo Manufacturing. Understanding these factors is crucial, as employee performance plays a pivotal role in achieving organizational objectives. The expected outcome is a deeper insight into the key drivers that enhance employee productivity. Methodology A quantitative approach was adopted using a descriptive-associative research design. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression via SPSS. Result: The findings reveal that both competence and resilience have a positive and significant effect on employee performance, both individually (partially) and jointly (simultaneously). Tindings: This study reveals that the combination of individual capability and psychological resilience directly contributes to improved employee performance. Novelty: This research offers a novel perspective by integrating psychological (resilience) and technical (competence) factors as joint determinants of employee performance in the manufacturing sector. Oriiginallity: The study is original in its focus on the interrelationship between competence and resilience within the context of Indonesia's manufacturing industry a perspective rarely explored in existing literature. Conclusion: Competence and resilience are significant predictors of employee performance. The findings provide a foundation for strategic human resource development efforts aimed at enhancing workforce effectiveness. Type of paper: Empirical Research Article